Tumor-related gene expression levels in thymic carcinoma and Type B3 thymoma. Issue 1 (December 2016) - Karube, Yoko; Kobayashi, Satoru; Maeda, Sumiko; Sado, Tetsu; Ishihama, Hiromi; Chida, Masayuki
Abstract Background Thymic carcinoma (TC) is a rare type of malignant neoplasm that develops in the anterior mediastinum and associated with poor prognosis. Type B3 thymoma (B3) occasionally demonstrates malignant tumor characteristics, especially in the advanced stage. We investigated the expressions of tumor-related genes in resected TC and B3 specimens. Methods TC and B3 specimens resected from 1999 through 2012 were investigated. Tumor segments were collected from the specimens by micro-dissection to extract mRNA, then RT-PCR was performed according to Dannenberg's tumor profile method for semi-quantitation of tumor-related gene mRNA. To compare with other types of cancer, data from lung cancer (LC) cases in our database were also examined. Results The gene expression levels of thymidylate synthase were significantly higher in TC and B3 as compared to LC specimens (p  < 0.02), while no difference were observed between TC and B3 tumors. The ratio of folypolyglutamyl synthase (FPGS) to gamma-glutamyl hydrolase (GGH) mRNA was significantly lower in TC than in B3 (p  < 0.05), with lower FPGS/GGH in those tumors related to overall survival. Also, the gene expression of vascular endothelial growth factor (VEGF) was significantly higher in TC as compared to B3 (p  = 0.04), with higher VEGF gene expression in TC and B3 specimens related to overall survival of affected patients. Epidermal growth factor receptor (EGFR) expression was significantly higher in B3 as compared to both TC and LC specimens (p  < 0.01). However, there were no EGFR gene mutations detected in any of the specimens. Conclusions These results indicate that elevated expressions of the tumor-related genes FPGS/GGH and VEGF are correlated with malignancy of TC and B3 tumors. Additional examinations will be necessary to investigate their chemosensitivity.